Ajudecumin A from Ajuga ovalifolia var. calantha exhibits anti-inflammatory activity in lipopolysaccharide-activated RAW264.7 murine macrophages and animal models of acute inflammation. (1st January 2018) - Zhang, Hai; Ren, Qing-Cuo; Ren, Yan; Zhao, Lin; Yang, Fan; Zhang, Yi; Zhao, Wen-Ji; Tan, Yu-Zhu; Shen, Xiao-Fei
Abstract: Context: Ajuga ovalifolia Bur. et Franch. var. calantha (Diels) C. Y. Wu et C. Chen (Labiatae), a traditional Chinese medicine, has been used to treat several inflammatory diseases. Objective: To assess the anti-inflammatory activity of ajudecumin A isolated from Ajuga ovalifolia var . calantha, and its possible mechanisms. Materials and methods: Lipopolysaccharide (LPS, 0.5 μg/mL)-stimulated RAW264.7 macrophages were used to assess the anti-inflammatory activity of ajudecumin A (1–40 μM) in vitro . Nitric oxide levels were evaluated by Griess reagent. The mRNA levels of iNOS, COX-2, TNF-α, IL-1β and IL-6 were determined using qRT-PCR. Phosphorylation of ERK, JNK, p38 MAPK and IκBα were detected by western Blot. To further assess the anti-inflammatory of ajudecumin A in vivo, mice were oral treated with ajudecumin A (10 mg/kg) or dexamethasone (0.25 mg/kg, positive control) for 5 days before administration of carrageenan or xylene. Paw and ear edema were then measured, respectively. Results: Ajudecumin A (10–40 μM) decreased LPS-induced nitric oxide production with an IC50 value of 16.19 μM. Ajudecumin A (20 and 40 μM) also attenuated cell spreading and formation of pseudopodia-like structures, and decreased the mRNA levels of iNOS (55.23–67.04%, p < 0.001), COX-2 (57.58–70.25%, p < 0.001), TNF-α (53.75–58.94%, p < 0.01–0.001), IL-1β (79.41–87.85%, p < 0.001) and IL-6 (54.26–80.52%, p < 0.01–0.001) in LPS-activated RAW264.7 cells. Furthermore, ajudecumin A suppressed LPS-induced phosphorylation of ERK, p38 MAPK, and IκBα, as well as IκBα degradation ( p < 0.05–0.001). Finally, ajudecumin A (10 mg/kg) attenuated carrageenan- and xylene-induced inflammation in mice by about 28 and 24%, respectively. Discussion and conclusions: Ajudecumin A exhibited a potent anti-inflammatory activity in vitro and in vivo through inhibition on NF-κB and ERK/p38 MAPK pathways, suggesting that ajudecumin A may be potentially developed as a lead compound in anti-inflammatory drug discovery.